2020
DOI: 10.1016/j.jenvman.2019.109826
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous sludge minimization, biological phosphorous removal and membrane fouling mitigation in a novel plant layout for MBR

Abstract: The integration of one anaerobic reactor in the mainstream (AMSR) of a pre-denitritication-MBR was evaluated with the aim to achieve simultaneous sludge minimization and phosphorous removal. The excess sludge production was reduced by 64% when the AMSR was operated under 8h of hydraulic retention time (HRT). The highest nutrients removal performances referred to organic carbon (98%), nitrogen (90%) and phosphorous (97%) were obtained under 8 h of HRT. In contrast, prolonged anaerobic-endogenous conditions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 36 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…The highest P-removal efficiency was achieved with 2-stage MLE having single internal recirculation from aerobic to anoxic zone and with addition of coagulant. The study of Corsino et al (2020) evaluated the nutrient removal performance of pre-denitrification A/O configuration with recirculation of 500% (5 times of the influent flow) from aerobic to anoxic tank. The authors found that the novel layout is capable to remove 97% of the phosphorus with addition of external carbon source and without addition of coagulant.…”
Section: Mbr Configurations and Treatment Sequence For P-removalmentioning
confidence: 99%
“…The highest P-removal efficiency was achieved with 2-stage MLE having single internal recirculation from aerobic to anoxic zone and with addition of coagulant. The study of Corsino et al (2020) evaluated the nutrient removal performance of pre-denitrification A/O configuration with recirculation of 500% (5 times of the influent flow) from aerobic to anoxic tank. The authors found that the novel layout is capable to remove 97% of the phosphorus with addition of external carbon source and without addition of coagulant.…”
Section: Mbr Configurations and Treatment Sequence For P-removalmentioning
confidence: 99%
“…Finally, the extracellular polymeric (EPS) content of the sludge was determined according to the literature (Corsino et al, 2020)…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, cell decay and EPS destructuration were observed in a membrane bioreactor (MBR) coupled with an anoxic side-stream reactor operating with 10 hours HRT (Fida et al, 2021). Corsino et al (2020b) found that when increasing the HRT in the ASSR from 6 h to 10 h, sludge minimization was mainly driven by endogenous decay, whereas the contribution of the uncoupling metabolism decreased. Nonetheless, Velho and co-authors observed that a 45% increase of the ASSR volume (HRT from 6 h to 10 h) did not promote a further reduction of excess sludge, since it was affected by other factors such as aerobiosis/anaerobiosis alternation (Velho et al, 2016).…”
Section: Introductionmentioning
confidence: 90%
“…According to these studies, prolonged fasting in anaerobic reactor forced bacteria to consume their conserved energy in form of adenosine-triphosphate (ATP). Once returned in the enriched-oxygen environment, the internal energy levels were restored and additional substrate consumption is promoted, thereby leading to an additional oxygen requirement (Semblante et al, 2014;Corsino et al, 2020b).…”
Section: Wastewater Characteristics and Main Operating Parametersmentioning
confidence: 99%